Предмет: Алгебра,
автор: gogavaynberg
помогите пожалуйста решить
Приложения:
Ответы
Автор ответа:
0
1) с-2 /с+2 - c/c-2= (c-2)(c-2) -c(c+2) /(c-2)(c+2)=c²-4c+4-c²-2c / (c-2)(c+2)=
=4-6c /(c-2)(c+2)
2)4-6c /(c-2)(c+2) * c+2 / 2-3c= 2(2-3c) /(c-2)(c+2) * c+2 / 2-3c= 2/ c-2
=4-6c /(c-2)(c+2)
2)4-6c /(c-2)(c+2) * c+2 / 2-3c= 2(2-3c) /(c-2)(c+2) * c+2 / 2-3c= 2/ c-2
Похожие вопросы
Предмет: Геометрия,
автор: gp5px3va9y
Предмет: Английский язык,
автор: Аноним
Предмет: Биология,
автор: reparod652
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: ielmurat